ANALISIS DAMPAK DIKELUARKANNYA KEBIJAKAN QUANTITATIVE EASING THE FED TERHADAP KURS RUPIAH/USD - Muliarta, I Gusti Ngurah Bagus Bayu Palguna; Widanta, Anak Agung Bagus Putu (Buletin Studi Ekonomi; VOLUME.28.NO.02.TAHUN.2023DO - 10.24843/BSE.2023.v28.i02.p06, 2023)
This study aims to analyze both domestic and foreign factors such as US interest rates, the Fed's quantitative easing policy and the IHSG which affect the dollar exchange rate against the rupiah in the short and long term. The analysis technique used in this study is ARDL (Auto-Regressive Distributed Lag). The data used in this study is in the form of secondary data in the monthly period in the form of time series data. The results showed that the Fed's interest rate at lag 0 had a negative and significant effect on the dollar exchange rate on the rupiah in the short term, the Fed's interest rates at lag-1 and lag-3 had a positive and significant effect on the dollar exchange rate on the rupiah in the short term. IHSG at lag-0 has a negative and significant effect on the dollar exchange rate against the rupiah in the short term. The Fed's quantitative easing monetary policy as a dummy variable has a positive and significant effect on the dollar exchange rate against the rupiah. In the long term, the results of the study show that the Fed's interest rate has a significant positive effect on the dollar exchange rate against the rupiah, while the JCI has a negative but not significant effect on the dollar exchange rate against the rupiah.